Influence of Training Load and Altitude on Heart Rate Variability Fatigue Patterns in Elite Nordic Skiers - Schmitt, Laurent; Regnard, Jacques; Coulmy, Nicolas; Millet, Gregoire P. (International Journal of Sports Medicine, 2018)
We aimed to analyse the relationship between training load/intensity and different heart rate variability (HRV) fatigue patterns in 57 elite Nordic-skiers. 1063 HRV tests were performed during 5 years. R-R intervals were recorded in resting supine (SU) and standing (ST) positions. Heart rate, low (LF), high (HF) frequency powers of HRV were determined. Training volume, training load (TL, a.u.) according to ventilatory threshold 1 (VT1) and VT2 were measured in zones I≤VT1; VT1<II≤VT2; III>VT2, IV for strength. TL was performed at 81.6±3.5% in zone I, 0.9±0.9% in zone II, 5.0±3.6% in zone III, 11.6±6.3% in zone IV. 172 HRV tests matched a fatigue state and four HRV fatigue patterns (F) were statistically characterized as F(HF-LF-)SU_ST for 121 tests, F(LF+SULF-ST) for 18 tests, F(HF-SUHF+ST) for 26 tests and F(HF+SU) for 7 tests. The occurrence of fatigue states increased substantially with the part of altitude training time (r2=0.52, p<0.001). This study evidenced that there is no causal relationship between training load/intensity and HRV fatigue patterns. Four fatigue-shifted HRV patterns were sorted. Altitude training periods appeared critical as they are likely to increase the overreaching risks.
Keywords: heart rate variability; fatigue; training load; endurance training; altitude training